Analisia Kegagalan Pengajaran Pendidikan Agama Islam secara Klasikal dalam Perspektif Komunikasi Verbal Monologis - Yenny Imro'atul Mufidah (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
Implementation of 2013 Curriculum in Indonesia with a scientific approach shows that most learning activities are directly related to communication. This study aims to describe: failure of teaching classical Islamic education in a monological verbal communication perspective. This research is